Serum natremia affects health-related quality of life in patients with liver cirrhosis: a prospective, single centre study - Wunsch, Ewa; Naprawa, Grzegorz; Koziarska, Dorota; Milkiewicz, Małgorzata; Nowacki, Przemysław; Milkiewicz, Piotr (Annals of hepatology, 2013)
Introduction. Hyponatremia is associated with high mortality and predicts hepatic encephalopathy but its effect on health-related quality of life remains to be established. Material and methods. In this study we prospectively analyzed the relationship between hyponatremia, clinical features and quality of life in a cohort of 116 patients with cirrhosis. Chronic Liver Disease Questionnaire and Medical Outcomes Study 36-Item Short Form Health Survey were performed to assess quality of life. Evaluation of hepatic encephalopathy included West-Haven criteria, Psychometric Hepatic Encephalopathy Score and Critical Flicker Frequency analysis. Severity of liver disease was assessed with Child-Pugh score and MELD. Univariate and multivariate analysis were implemented to evaluate the influence of analyzed factors on quality of life. Results. Multivariate analysis has identified serum natremia, Psychometric Hepatic Encephalopathy Score, Critical Flicker Frequency and severity of liver disease measured with MELD and Child-Pugh score as independent factors affecting quality of life in patients with cirrhosis. West Heaven criteria failed to show the relationship with quality of life in analyzed subjects. Serum kalemia showed correlation with neither quality of life, hepatic encephalopathy nor severity of the disease. Conclusion. In patients with cirrhosis serum natremia along with severity of liver disease and hepatic encephalopathy exerts a significant effect on patients’ quality of life.